Effect of in-process cooling on microstructure and mechanical properties of dissimilar AA2014 and AA7075 friction stir welded joints - Kumar R.; Upadhyay V.; Misra J.P.; Sharma C. (My University, 2025)
Heat-carrying capacity of a cooling medium is critical as it governs microstructure evolution and tensile properties during friction stir welding (FSW). In this research, three cooling techniques: conventional air-cooling (CAC), forced air-cooling (FAC), and water flow cooling (WFC), were employed to study the effect on microstructure and mechanical properties in dissimilar FSW of AA2014 and AA7075. In-process cooling significantly influenced weld microstructure, zone size, microhardness, and tensile properties, which varied with the cooling medium. Water flow cooling was the most effective cooling technique due to its higher heat carrying capacity than CAC and FAC. Water flow cooling resulted in a drastically refined grains structure of smaller size in all zones, had higher tensile strength, elongation, and heat-affected (HAZ) hardness than CAC and FAC. Greatly refined grain structure and less dissolution of precipitates in weld nugget zone (WNZ) along with smaller HAZ and thermo-mechanically affected zone (TMAZ) are responsible for improved weld properties of WFC than the FAC and CAC. Forced air-cooling resulted in a higher microhardness value at WNZ, followed by WFC and CAC. Fractured surfaces of the tensile specimen were scrutinized by scanning electron microscope. Cooling did not affect the fracture side and location; however, fracture mode changed with cooling medium viz. ductile for FAC and WFC and mixed-mode for CAC. © IMechE 2022.